Безпека у сучасних готелях - Сірик, Аліна Олегівна; Свірська, Інна Вячеславівна; Вербова, Юлія Володимирівна (My University, 2014)
Сучасний готель оснащений різноманітним обладнанням і майном. У ньому працює значна кількість обслуговуючого персоналу, відбувається постійна зміна гостей. Саме тому питаннями охорони праці, техніки безпеки та пожежної безпеки в закладах готельного господарства приділяється велика увага. The hotels have a variety of equipment and property. It has a large number of service personnel, the constant change of guests. That is why issues of labour protection, safety engineering and fire safety in places of hospitality industry pays a lot of attention. The relevance of the chosen topic due to the stringent requirements of legislation in the field of health and safety, expanding the hotel complexes on the territory of Ukraine and cases of accidents in crowded places.
Keywords: сучасний готель; обслуговуючий персонал; техніка безпеки; аварійна ситуація; hotel; catering staff; safety; emergency; кафедра екології та екоменеджменту